2023
DOI: 10.3390/metabo13070789
|View full text |Cite
|
Sign up to set email alerts
|

Açaí (Euterpe oleracea Mart.) Seed Oil Exerts a Cytotoxic Role over Colorectal Cancer Cells: Insights of Annexin A2 Regulation and Molecular Modeling

Abstract: Açaí, Euterpe oleracea Mart., is a native plant from the Amazonian and is rich in several phytochemicals with anti-tumor activities. The aim was to analyze the effects of açaí seed oil on colorectal adenocarcinoma (ADC) cells. In vitro analyses were performed on CACO-2, HCT-116, and HT-29 cell lines. The strains were treated with açaí seed oil for 24, 48, and 72 h, and cell viability, death, and morphology were analyzed. Molecular docking was performed to evaluate the interaction between the major compounds in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…Silva et al [ 49 ] aimed to analyze the effects of açai seed extract and oil ( Euterpe oleracea Mart.) on different human colon adenocarcinoma cell lines (Caco-2, HT-29, and HCT-116).…”
Section: Biological Effects Of Fruits Of Amazonian Palm Treesmentioning
confidence: 99%
“…Silva et al [ 49 ] aimed to analyze the effects of açai seed extract and oil ( Euterpe oleracea Mart.) on different human colon adenocarcinoma cell lines (Caco-2, HT-29, and HCT-116).…”
Section: Biological Effects Of Fruits Of Amazonian Palm Treesmentioning
confidence: 99%
“…Monge-Fuentes et al (2017) demonstrated that açaí oil inhibited cell viability in B16F10 murine melanoma cell lines by 85% through apoptosis [9]. Similarly, Da showed that both the extract and the seed oil exhibited cytotoxic effects on colorectal adenocarcinoma cell lines CACO-2, HCT-116, and HT-29 [22].…”
Section: Introductionmentioning
confidence: 99%